Challenges and Strategies of Teaching Arabic and French Literature in Nigeria - Mikail Adebisi Folorunsho; Rabiu Olayinka Iyanda (TRANS-KATA: Journal of Language, Literature, Culture and Education, 2022)
The issue of appropriate methodology for suitable teaching of literature of Arabic and French in Nigerian schools has continued to receive attention from educationists on how to make it more beneficial to society. Literature is to be for life’s sake; therefore, its teaching should be able to assist in solving day-to-day problems. This paper discovered and discussed the obstacles militating against effective Arabic and French language literature teaching. It discovered the prominent obstacles confronting effective teaching of the literature of these languages to be the shortage of competent teachers, non-availability of suitable textbooks, lukewarm attitude to the languages on the parts of the learners, and the parents and acute dearth of suitable instructional materials. The paper is survey research, deriving its sources from an extensive consultation of relevant literature and interaction with the stakeholders. While it should be stated that each language has its peculiarities, they have some common grounds. One of such common grounds is the application of the same methodology to some aspects of the two languages. It suggested a possible methodology to perfect the teaching and make the learners achieve the desired goals. Of the three genres of literature (prose, drama, and poetry), drama and prose were treated because they share numerous similarities. Teaching and understanding Arabic and French literature in Anglophone nations like Nigeria with a workable methodology yielded desired outcomes.